2012
DOI: 10.1109/jlt.2012.2213238
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Instantaneous Microwave Analysis by Parametric Channelized Receiver Through Time Domain Monitoring

Abstract: For many applications, ranging from commercial, surveillance, or defense, it is essential to analyze the frequency components of a captured microwave signal over a wide bandwidth in real time and with high resolution. Various photonic approaches have been proposed for the processing of wideband microwave signals in order to overcome limitations imposed by conventional electronic frequency measurements. Here, we present the performance analysis and characterization of a parametric channelized receiver with 275 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Previous experiments on BOA failure showed that highly vibrationally excited molecules exhibit efficient vibrational relaxation when they collide with a clean single-crystal metal surface, whereas little relaxation is seen with insulators (14,15). This comparison showed the importance of electronic excitation by molecular vibration, a phenomenon that could also be investigated with first-principles theory (16,17).…”
Section: Electron-hole Pair Excitation Determines the Mechanism Of Hy...mentioning
confidence: 65%
See 1 more Smart Citation
“…Previous experiments on BOA failure showed that highly vibrationally excited molecules exhibit efficient vibrational relaxation when they collide with a clean single-crystal metal surface, whereas little relaxation is seen with insulators (14,15). This comparison showed the importance of electronic excitation by molecular vibration, a phenomenon that could also be investigated with first-principles theory (16,17).…”
Section: Electron-hole Pair Excitation Determines the Mechanism Of Hy...mentioning
confidence: 65%
“…1). In the optical domain, the received spectrum can be parametrically cloned (8) and subsequently decomposed by a single physical filter (14). This strategy cannot be applied in spectral ranges where efficient, low-noise parametric mixers (15,16) do not exist.…”
mentioning
confidence: 99%